Gene expression profile, and anatomical and physiological characteristics of Ga inhibitor (Paclobutrazol) - treated oil palm (Elaeis guineensis Jacq.) in nursery condition - Abdul Rahman, Mohd Nasriq Hafizee (2016)
Oil palm, the major crop planted in Malaysia, becomes one of the important commodity crops with a total planted area of 5.4 million hectares in 2015. The economic value of oil palm is determined by its height, since the height of a tree will influence the cost of harvesting the fresh fruit bunch (FFB). The increase of oil palm height will increase the difficulty and may cause damages to FFB during harvesting process. Thus, this study was conducted in effort to manipulate the oil palm height (stem elongation) through the manipulation of plant growth hormones by using GA Inhibitor (paclobutrazol). The main objective of this research was to investigate the effect of paclobutrazol (PBZ) on genes expression pattern, physiological and anatomical characteristic of oil palm (Elaeis guineensis) in nursery condition. Oil palm in each treatment were grown under nursery condition and were treated with different concentration ofPBZ ranging from 10 mgl." to 100 mgl," by using foliar spray. After six weeks of PBZ treatment, material from leaves and stem were extracted for genes expression analysis and histological observation using light microscope. Oil palm treatment with PBZ resulted in short and dwarf plant with dark green leaves and smaller stem diameter compared to control. Furthermore, leaves of treated oil palms showed an increment in photosynthesis rate and chlorophyll index with larger and shorter mesophyU palisade cell compared to control plant. PBZ treatment course parenchyma cell in the stem to grow shorter and smaller compared to control. On the other hand, basal cell showed increment in cell diameter in response to PBZ treatment, while there was no difference in term of basal cell height can be observed between PBZ treated and control plant. In addition, PBZ treated oil palm showed remarkable increment on starch granule accumulation in parenchyma cell of oil palm stem. By using in-silico analysis, we identified a two oil palm putative GA biosynthesis related genes which were GA2 (EgGa2ox) and GA20-oxidase (EgGa20ox). The data revealed that, PBZ treatment does not affect the expression profiles of EgGA20x and EgGA200x in leaf tissues as all two putative GA oxidase genes show a consistent value of relative band intensity (RBI) compared to the controls. On the other hand, the expressions of EgGA20x and EgGA200x slightly drop in PBZ treated oil palm stem. These results suggest that PBZ may have various effects on the GA oxidase levels from different parts of oil palm tissues. In summary, PBZ treated oil palm had modified genes expression pattern, physiological and anatomical characteristic of the plant depending on PBZ concentration applied and plant parts. In addition, PBZ treatment also facilitates the enhancement of net photosynthesis rate, chlorophyll content and starch accumulation in oil palm tissues.